By the Honourable Jonathan Trumbull, Esquire, Governor, Captain-General, and Commander in chief in and over the state of Connecticut, in America ; a proclamation for a day of fasting and prayer : ... Thursday, the 24th day of April next ... Given under my hand in Lebanon, the 29th day of March ... one thousand, seven hundred and seventy-seven (Printed by Timothy Green, printer to the Governor and Company, 1777)
March 29, 1777 broadside issued by Governor Jonathan Trumbull of Connecticut, proclaiming April 14th as a day of fasting and prayer because of the war.